Biologically Inspired Cognitive Architectures 2018 Proceedings of the Ninth Annual Meeting of the BICA Society - Samsonovich, Alexei V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book focuses on original approaches intended to support the development of biologically inspired cognitive architectures. It bridges together different disciplines, from classical artificial intelligence to linguistics, from neuro- and social sciences to design and creativity, among others. The chapters, based on contributions presented at the Ninth Annual Meeting of the BICA Society, held in on August 23-24, 2018, in Prague, Czech Republic, discuss emerging methods, theories and ideas towards the realization of general-purpose humanlike artificial intelligence or fostering a better understanding of the ways the human mind works. All in all, the book provides engineers, mathematicians, psychologists, computer scientists and other experts with a timely snapshot of recent research and a source of inspiration for future developments in the broadly intended areas of artificial intelligence and biological inspiration.
Keywords: Computational intelligence; Artificial intelligence; Neurosciences; Cognitive psychology; Biometric identification; Computational Intelligence; Artificial Intelligence; Neuroscience; Cognitive Psychology; Biometrics